Enjoy your evening, be proactive tomorrow: How Off-Job experiences shape daily proactivity - Ouyang, K.; Cheng, B.H.; Lam, W.; Parker, Sharon (AMER PSYCHOLOGICAL ASSOC, 2019)
© 2019 American Psychological Association.